Measuring gender equality in technical and vocational education and training - Mohamad, M. M.; Sulaiman, N. L.; Sern, L. C.; Mohd Salleh, K. (Penerbit Akademia Baru, 2015)
This study was performed to measure the gender equality involvement in Technical and Vocational Education and Training (TVET) Program in one of the Malaysia Technical University Network (MTUN). The focuses of this study are general perspective in gender equality, men and women position in society, and sources of information about TVET. 200 respondents involving students and lecturers from various field of TVET programs involved in this study. Questionnaire was applied to gather the data information and descriptive analysis represent the findings. Result showed that most respondents strongly agree with men helping in the household were women, they are also aware about the national policies on gender equality in Malaysia, and for last section of survey, respondents agree that they choose studying in TVET program because the better job opportunities. In summary, there is no gender issue in Malaysia’s policy, position of work and opportunities in further education especially in TVET programs.